Pro-inflammatory cytokine level and neutrophil count in acute ischemic stroke - Suroto, Suroto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Pro-inflammatory cytokines are cytokines which are often found to be increased in an inflammatory process. In acute ischemic stroke there is an inflammatory response which affects the progress of the stroke.Objectives: The aim of this study was to understand the correlation between pro-inflammatory cytokines and neutrophil count in the peripheral blood of acute ischemic stroke patients.Methods: Peripheral blood was taken from 30 acute ischemic stroke patients age 50-70 years old on the third day of stroke attack. Leukocytes and differential count were examined, also level of TNF alpha, IL-1 and IL-8. Confirmation of ischemic stroke was determined by the head CT scan without contrast media on the fourth day of stroke attack. Thirty subjects without stroke were taken as control, with matching in age, gender and ethnic group.Results: The result showed a significant difference in neutrophil count between stroke group and control group (F 0.001). There was also significant difference among the 3 pro-inflammatory cytokines in 2 groups (F for TNF alpha: 0.007, IL-1: 0.055 and IL-8: 0.002). In bivariate correlation test, there was a significant correlation between IL-8 level and neutrophil count in the blood (p 0.0000).Conclusion: It is concluded that pro-inflammatory cytokines especially IL-8 has a role in recruiting neutrophil as an important component in the inflammatory response in acute ischemic stroke.Keywords: ischemic stroke - pro-inflammatory cytokines - IL-8 - neutrophil - correlation